A STUDY OF REASONS OF NON-COMPLIANCE TO PSYCHIATRIC TREATMENT - Taj, Rizwan; Khan, Saleem (Journal of Ayub Medical College Abbottabad, 2005)
Background: This study was carried out with an objective to find out the frequency of different reasons of non-compliance to treatment in a sample of out door psychiatric patients. Methods: This study was conducted at Psychiatry department, Pakistan Institute of Medical Sciences, Islamabad, from Aug, 2001 to Jan, 2002. Data from a non-probability sample of two hundred follow up patients with a definite psychiatric illness was collected. A questionnaire designed for this purpose was administered by a consultant psychiatrist to the patients. The data was categorized into different causes of discontinuation of treatment accordingly. Results: The commonest reasons for non-compliance were unawareness of the benefits of treatment (43%), nonaffordability of drugs (33.5%), physical side effects (28.5%), no awareness given by the doctor (03%) and unfriendly attitude of doctors (02%). The commonest illnesses leading to non-compliance were major depressive disorder (31.5%), schizophrenia (19.5%) and bipolar affective disorder (19%). Conclusion: Non-compliance is quite common in Pakistan like any other society. Medical practitioners need to be aware of it and address this problem because compliance is directly related to the prognosis of the illness. It is recommended that all efforts should be exerted to improve the compliance of psychiatric patients by eliminating the factors leading to non-compliance. KEYWORDS: Non-compliance, Psychiatric illnesses, Treatment.